Systematisation of university students’ physical fitness using a software module - Prokhorenko, A.A.; Kolesnikov, N.V.; Antonov, A.V.; Yakovlev, G.A. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to substantiate and implement a software module for the systematisation and monitoring of physical fitness levels among university students. Methods and structure of the study. The following research methods were employed: literature review, data collection, questionnaire survey, and mathematical processing of research results. Based on the analysis of regulatory legal acts, the necessity of introducing innovative teaching technologies into the educational process was established. A questionnaire survey revealed that the use of a software module for the systematisation and monitoring of physical fitness levels is in demand among students and constitutes an important factor in increasing motivation for physical education classes. Results and conclusions. The software module for the systematisation and monitoring of physical fitness levels among university students promotes the development of students’ physical qualities and enhances the quality of education.